ISOLATION AND IDENTIFICATION OF MICROBES FROM BUFFALO (BUBALUS BUBALIS) DUNG - Longjam Olympia Devi1, Praveen Kumar Gautam2, Indu Sharma1*, (Chelonian Research Foundation, 2023)
The domestic cattle’s cows, bullocks, and buffalo are bovine animal species, which comprises domestic cattle (cows, bullocks, and buffalo), produce dung, also known as manure. Buffalo dung microbial community and its relationship to the rumen microbiome of the animal. The buffalo microbiome appears to have more capability for fibre degradation and less potential for methane production when compared to the rumen microbiomes of other cattle. Microbial load of buffalo dung having Bacillus, Fibrobacter, Ruminococcus, Pseudomonas aeruginosa, Enterobacter xiangfangensis, Proteus mirabilus, Butyrivibrio and Prevotella, capable of degrading non-cellulose plant ﬁbres, is abundantly present in the rumen in buffalo digestive tract. In the present study microbial load of buffalo dung was analyzed by using nutrient agar, blood agar and MacConkey agar, Sabouraud Dextrose Agar (SDA). The properties of the isolated bacteria's colonies and Gram's staining were observed. Buffalo dung microbial load was calculated using the number of cfu per gram of sample. The highest bacterial population was seen at dilution 10-3, where it reached ranged from 155×10-4cfu/ml. Total 20 bacterial isolates were isolated from buffalo dung including Gram Positive cocci, Gram Positive bacilli and Gram Negative bacilli. These bacterial isolates were identified as Microccocus sp. Bacillus sp. and Escherichia coli respectively. Sabouraud Dextrose Agar (SDA) used for fungal isolation. The fungal colonies of Rhizopus sp. (F1) was exhibited in dilution 10-2 which ranged 30×10-3 cfu/ml. These microbes will be used forfurther research work. Keywords: Buffalo dung, Microbial load, Bacteria, Fungi, Microbiome.